Thermal conductivity studies on magnetite nanofluids coated with short-chain and long-chain fatty acid surfactants - Lenin, R.; Dadwal, A.; Joy, P. A. (Bulletin of Materials Science, 2018)
The effect of the length of surfactant molecules on the surface of the nanoparticles on the thermal conductivity of nanofluids is studied. Magnetite (Fe3O4) nanoparticles of comparable sizes are stabilized with short-chain capric acid (C9H19COOH) and long-chain stearic acid (C17H35COOH) molecules. Thermal conductivity of the two surfactant-coated magnetite nanoparticles dispersed in toluene is measured as a function of the concentration of the particles in the fluids and in the presence of a magnetic field. Studies showed that the critical concentration for thermal conductivity enhancement is lower for stearic-acid-coated fluid as compared with the capric-acid-coated fluid. Comparable enhancement in the thermal conductivity is observed at higher concentrations of the particles. Relatively larger enhancement in the thermal conductivity is observed for the capric-acid-coated fluid in a magnetic field. The difference in the enhancement in the thermal conductivity, depending on the chain length of the surfactant, is explained in terms of the inter-particle magnetic interactions and formation of clusters.